Pendekatan Clustering Budaya Organisasi dalam Upaya Peningkatan Kinerja Karyawan - Nurvi Oktiani; Camelia Putri Utami; Kartika Yuliantari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
Organization culture is a concept with multidimensional characteristic which consists of belief, values, and behavior pattern an assumption, that can be spread to organization, in other hand organization culture is one of element with have specific characteristic that can be improved quality and change in process management of organization performance, the research uses qualitative and qualitative design, data have been collected by observation, interview, and questionnaire. Data Analytic Technique uses factor analytic with other calculation, for other calculation, this research uses some indicator in organization culture, and it has been classified for some cluster consist of Constructive Cluster, Passive or Defensive cluster, and Aggressive cluster. The Result of research can be described some indicator of organization culture are constructive cluster consist of innovation, Information, and technology benefits, new methods, loyalty and belief, transparent and openness, in other hands passive or defensive cluster, consists of evaluation and controlling, monitoring system, opportunities for increased performance, change, and service of organization and aggressive cluster consist of opportunities for  carrier development, self -  improvement, empathy